Analysis of Outcome Based Education (OBE) Program Development: Case Study of Master of Economics Study Program UPN “Veteran” Yogyakarta - Wijayanti, Diah Lufti; Suharsih, Sri; Rahayu, Astuti (RSF Conference Series: Business, Management and Social Sciences, 2021)
The purpose of this study was to analyze the position and problems faced by the study program in implementing the tri dharma of higher education. The analysis is carried out by conducting direct data reviews, both internally and externally. This study used several respondents consisting of stakeholders of the Master of Economics (MIE) study program. The analytical tools used include the IFE and EFE Matrix, SWOT analysis. The results of the study state that the MIE study program must make improvements in the process of implementing the tri dharma with the carrying capacity of the study programs and institutions. The need for integration in every tri dharma activity so that based on the track record of study program data, development can be carried out according to the approach used.